Թխվածք հասկացույթի արտացոլման ազգային առանձնահատկությունները հայերենում և անգլերենում - Փաթյան, Կ.
В этой статье мы обращаем особое внимание на анализ понятия cake и թխվածք (сладость) на основе их фразеологических единиц в армянском и английском языках. Концепт, который имеет много интересных ассоциации в армянском, едва имеет соответствующие обьяснения на английском и любых других языках. Мы знаем, что языки разные по их словарному запасу. Такие различия остаются за смысловыми границами культурных обьектов. In this article we pay special attention to the analysis of the concepts cake and թխվածք on the basis of their phraseological units in English and Armenian. The concept which has very many interesting associations in Armenian, will hardly have appropriate explanations in English and in any other language besides it. We know that languages are different according to their vocabulary. Such differences are out of the sense boundaries of cultural objects.
Keywords: Լեզվաբանություն